THE USE OF TECHNOLOGY TO INTEGRATE BIOLOGY AND MATHEMATICS - Sonmez, Duygu; Özgün-Koca, S. Asli (International Online Journal of Education and Teaching, 2024)
STEM education, pivotal for 21st-century skills development, requires effective integration of its disciplines, wherein purposeful technology use is essential. This paper explores the roles of technology in integrating biology and mathematics, utilizing Goos et al.’s (2000, 2003) conceptual framework, which categorizes technology as master, servant, partner, and extension-of-self. The study emphasizes the roles of technology as a servant and a partner, presenting various technologies, both hardware and software, that facilitate this integration. It provides examples from two lessons designed for middle school students and preservice science teachers. These examples illustrate the practical application of technology in educational settings, demonstrating how it functions as a servant to perform tasks efficiently and as a partner to enhance and support learning. The paper discusses the design and implementation of these lessons, highlighting the educational benefits and potential challenges of integrating technology into STEM curricula. Through these case studies, the paper underscores the importance of strategic technology use in creating interdisciplinary STEM lessons that foster deeper student understanding and engagement.